2011
DOI: 10.1021/es2002748
|View full text |Cite
|
Sign up to set email alerts
|

Strong Enhancement on Fenton Oxidation by Addition of Hydroxylamine to Accelerate the Ferric and Ferrous Iron Cycles

Abstract: The Fenton system generates reactive species with high oxidation potential such as hydroxyl radicals (HO(•)) or ferryl via the reaction between Fe (II) and H₂O₂. However, a number of drawbacks limit its widespread application including the accumulation of Fe (III) and the narrow pH range limits, etc. The aim of this study is to propose a much more efficient Fenton-HA system which is characterized by combining Fenton system with hydroxylamine (NH₂OH), a common reducing agent, to relieve the aforementioned drawb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
168
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(177 citation statements)
references
References 36 publications
7
168
0
2
Order By: Relevance
“…Moreover, the steady-state concentration of Fe(III) could be attributed to dynamic equilibrium of the iron ion circulation given in Eqs. (3)- (5) (Chen et al, 2011;Han et al, 2014). The higher steady-state concentration of Fe(III) in the system with SMX was probably due to the influence of target organics and intermediates on the UV absorption of solution at 300 nm.…”
Section: Role Of Ha In Ha/fe(ii)/pms Processmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, the steady-state concentration of Fe(III) could be attributed to dynamic equilibrium of the iron ion circulation given in Eqs. (3)- (5) (Chen et al, 2011;Han et al, 2014). The higher steady-state concentration of Fe(III) in the system with SMX was probably due to the influence of target organics and intermediates on the UV absorption of solution at 300 nm.…”
Section: Role Of Ha In Ha/fe(ii)/pms Processmentioning
confidence: 98%
“…Then increasing HA concentration continuously from 0.4 to 1.0mM, the improvement on the removal of SMX was found to be insignificant. Authors (Chen et al, 2011;Zou et al, 2013) reported that HA could effectively promote the redox cycle of Fe(III) to Fe(II), improve the generation of reactive species and increase the removal of organic pollutants at pH 3.0. However, excess HA could quench the reactive species (e.g., SO4…”
Section: Role Of Ha In Ha/fe(ii)/pms Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, many technologies have been developed to improve Fenton oxidation for removing organic contaminants from aqueous solutions, such as photo-assisted (Al Momani et al, 2006;Kusic et al, 2006;Lau et al, 2002), microwave-enhanced (Liu et al, 2013;Yang et al, 2009), heating (Pliego et al, 2012;Zazo et al, 2011), and quinone (Chen and Pignatello, 1997;Gomez-Toribio et al, 2009) and hydroxylamine hydrochloride (HA) (Chen et al, 2011) redox cycling. As mentioned above, a major drawback of the Fenton system has been the accumulation and hydrolysisprecipitation of ferric ions, which could further slow down the whole Fenton process.…”
Section: Introductionmentioning
confidence: 99%